Prognostic and immunological landscape of DDX17 in pan-cancer analysis: a comprehensive study - Yu Lei; Xin He; Peng Chen; Yiping Qin; Bin Ge; Yan Liu; Pu Li; Xing Wei (Discover Oncology)
Abstract Objective DDX17, an ATP-dependent RNA/DNA helicase, is implicated in the regulation of RNA metabolism and has been linked to tumorigenesis and metastasis in various cancers. While studies have explored the role of DDX17 in specific cancers, further research is needed to understand its mechanisms across different cancer types. Methods We leveraged several public databases, including TIMER, The Cancer Genome Atlas (TCGA), and the Genotype-Tissue Expression (GTEx), to investigate DDX17 mRNA expression across 33 types of tumors. The GEPIA2 database was utilized to assess the impact of DDX17 on overall survival (OS) and disease-free survival (DFS) in patients with these tumors. Additionally, we employed cBioPortal to examine DDX17 gene alterations in various tumor tissues. Further analysis was conducted using the R language to explore the correlation between DDX17 and a range of clinical features, including tumor microenvironment (TME), immune regulatory genes, immune checkpoints, tumor mutational burden (TMB), microsatellite instability (MSI), DNA methylation, RNA methylation, and drug sensitivity. Gene Set Enrichment Analysis (GSEA) was also applied to elucidate the molecular mechanisms mediated by DDX17. Results DDX17 showed significant differences in expression between cancer and normal tissues. Expression of DDX17 was associated with patient prognosis, TMB, MSI, and drug sensitivity in certain cancers. DDX17 is additionally involved in modulating immune functions and influencing the tumor microenvironment. Further analysis of DDX17 mutation sites and types showed that the mutation frequency was highest in endometrial cancer and the major mutations of DDX17 were missense mutations. Conclusion These findings indicated that DDX17 may be considered a potential prognostic biomarker and a promising target for novel immunotherapeutic approaches in cancer treatment.